EFFICACY OF Ficus congensis Engl. LEAF POWDER AGAINST PESTS OF STORED Tamaridus indica L. FRUITS IN GOMBE STATE, NIGERIA - ABBA, H. M; MUHAMAD K.U (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
An investigation was undertaken with the aim of determining the efficacy of Ficus congensis Engl. leaf powder against pests on stored Tamaridus indica L. fruits in Gombe State, Nigeria The experiment was conducted in the laboratory of the Department of Botany, Gombe State University. The method used was by obtaining the plant powders and thoroughly mixing with 20g of Tamarind fruits in 250ML plastic containers at, 0.2, 0.4 0.6 and 0.8g concentrations according standard procedures. The findings revealed that the LC50, LC90 and LC99 had been found as 0.62g, 1.1g and 1.2g respectively which varied according to Concentrations of and duration of exposure, The treatments had significant results compared to the controls at P≤0.05 level of significance using the Student Newman-Keuls (SNK) test for variables. This study concluded that the high efficacy of organic pesticides Ficus congensis in the control of insect pest (Sitophilus linearis) was 85% mortality for four weeks. The study therefore recommended that Ficus congensis should be used at high Concentrations of 1.2 grams per 20 grams of Tamarind fruits to cause 99% mortality. Also the powder should be applied on fresh dried Tamarind fruits for efficient results as it has no toxic effect. The leaf powder is therefore recommended for Tamarind storage for at least four weeks.